Anharmonic lattice dynamics of superionic lithium nitride. Issue 5 (1st November 2021) - Krenzer, Gabriel; Kim, Chang-Eun; Tolborg, Kasper; Morgan, Benjamin J.; Walsh, Aron
Abstract : We explore the crystal vibrations of Li3 N and their connection to the high-temperature superionic transition. Abstract : Superionic crystals reach an ionic conductivity comparable to liquid electrolytes following a superionic transition at high temperature. The physical mechanisms that lead to this behaviour remain poorly understood. It has been proposed that superionic transitions are accompanied by the breakdown of specific phonon modes linked to characteristic diffusion processes. Any changes in vibrational properties across the superionic transition may therefore provide insights into the underlying physics of this phenomenon. Here, we apply a combination of lattice dynamics and ab initio molecular dynamics to probe the vibrational properties of the archetypal superionic conductor Li3 N. We assess harmonic, quasi-harmonic, and anharmonic descriptions of the phonons. The harmonic and quasi-harmonic models show no change in features across the superionic transition. The anharmonic model, however, exhibits a breakdown for all modes. The implications for developing lattice-dynamics-based descriptors for superionic conductors are discussed.